INNOVATIVE KNOWLEDGE MANAGEMENT STRATEGIES TRANSFORMING ORGANIZATIONAL SUCCESS - Wijaya, Yoana Sonia; Haryani, Calandra A.; Hery, Hery; Widjaja, Andree E.; Tarigan, Riswan E. (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
In the current information technology era, knowledge management plays a critical role in the growth and success of enterprises. Knowledge management techniques are not used in the same manner as previously due to advancements in technology. Current knowledge management practices can benefit greatly from the application of emerging technological trends like web 2.0, social networks, wikis and blogs, discussion forums, and artificial intelligence. This will increase organizational performance and efficiency. The purpose of this study is to investigate the growing influence of knowledge management techniques on organizational effectiveness. This study examines earlier research on the subject of how organizational performance is impacted by emerging trends in knowledge management strategies. The literature review approach, or literature study from earlier research publications linked to this topic, was the research method used in this study. The research findings are presented in the form of a model, which suggests that increasing organizational performance and competitiveness is positively and significantly correlated with the introduction of new trends in knowledge management methods. Organizations can increase their performance and competitiveness in a market that is becoming more and more competitive by implementing effective knowledge management methods, according to the implications of this research.